Serum inflammatory markers and leukocyte profiles accurately describe hidradenitis suppurativa disease severity. (11th May 2022) - Andriano, Tyler M.; Benesh, Gabrielle; Babbush, Kayla M.; Hosgood, H. Dean; Lin, Juan; Cohen, Steven R.
Abstract: Background: Inflammatory markers and leukocyte profiles have not been longitudinally evaluated as objective signs of hidradenitis suppurativa (HS) severity. We sought to assess C‐reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin‐6 (IL‐6), and leukocyte profiles as reliable indicators of HS severity. Methods: Retrospective cohort study of 404 patients seen at the Einstein/Montefiore HS Center, Bronx, New York, between March 2019 and November 2020. Associations of disease severity (HS‐Physician Global Assessment) with inflammatory markers and leukocyte profiles were assessed by odds ratios (OR) and 95% confidence intervals (95% CI) incorporating up to four visits per patient, adjusting for baseline gender, age, BMI, and smoking status. Results: Patients with severe disease had elevated CRP (OR 1.87; 95% CI 1.49, 2.34), ESR (OR 1.04; 95% CI 1.03, 1.04), IL‐6 (OR 1.08; 95% CI 1.00, 1.16), leukocytes (OR 1.22; 95% CI 1.14, 1.31), neutrophils (OR 1.31; 95% CI 1.20, 1.42), eosinophils (OR 14.40; 95% CI 2.97, 69.74), basophils (OR 2.53; 95% CI 1.09, 5.85), monocytes (OR 5.36; 95% CI 2.49, 11.53), and neutrophil‐lymphocyte ratios (OR 1.63; 95% CI 1.35, 1.96) but decreased lymphocytes (OR 0.86; 95% CI 0.68, 1.10). Conclusions: This novel longitudinal study of inflammatory markers and leukocyte profiles offers critical laboratory measures to confirm clinically determined disease severity over time.